Exploring HPV-linked head and neck cancer in Southern Punjab, Pakistan: Insights from HPV-16 phylogenetic analysis - Muhammad Kashif, PhD; Sadia Minhas, PhD; Shah Jahan, PhD; Faheem Shahzad, PhD; Romeeza Tahir, PhD; Afia Abbas, MSc; Muhammad Idrees, PhD; Nadeem Afzal, PhD (Journal of Taibah University Medical Sciences)
الملخص: أهداف البحث: سرطان الخلايا الحرشفية في منطقة الرأس والرقبة هو مرض غير متجانس ويمكن تصنيفه إلى نوعين فرعيين: إيجابي لفيروس الورم الحليمي البشري (20%) وسلبي لفيروس الورم الحليمي البشري (80%). ومع ذلك، فإن انتشار النمط الجيني لفيروس الورم الحليمي البشري في باكستان غير معروف جيدا. تهدف هذه الدراسة إلى بحث مدى شيوع النمط الجيني لفيروس الورم الحليمي البشري-16 في مرضى سرطان الخلايا الحرشفية في منطقة جنوب البنجاب في باكستان وما هي السمات الجزيئية المحددة التي يظهرها هذا النمط الجيني. طرق البحث: في هذه الدراسة المقطعية، جمع الباحثون 85 عينة أنسجة من حالات تم تشخيصها بسرطان الخلايا الحرشفية في منطقة الرأس والرقبة. لاستخراج الحمض النووي الجينومي، تم استخدام مقاطع الأنسجة المضمنة بالبارافين المثبتة بالفورمالين. وللكشف عن الحمض النووي لفيروس الورم الحليمي البشري، تم تضخيم المنطقة L1 باستخدام بادئات GP5+ وGP6+. تم استخدام تفاعل البوليميراز المتسلسل في الوقت الحقيقي لتحديد النمط الجيني لفيروس الورم الحليمي البشري عالي الخطورة. تم استخدام تسلسل الجينوم الكامل للتحليل التطوري والطفري لفيروس الورم الحليمي البشري-16. النتائج: من بين 85 عينة، كانت 7.1% إيجابية لفيروس الورم الحليمي البشري، مع 4.7% إيجابية لفيروس الورم الحليمي البشري-16 و2.4% إيجابية لفيروس الورم الحليمي البشري-18. كما كان هناك ارتباط كبير بين فيروس الورم الحليمي البشري عالي الخطورة الإيجابي والدرجة النسيجية. كان جينوم فيروس الورم الحليمي البشري-16 في الدراسة وثيق الصلة بتلك الموجودة في تايلاند والولايات المتحدة والهند والصين وأوروبا، وتم الكشف عن إجمالي 11 طفرة في الجينوم، منها أربع طفرات جديدة. الاستنتاجات: تشير نتائج الدراسة الحالية إلى انتشار نادر لسرطان الخلايا الحرشفية للرأس والرقبة المرتبط بفيروس الورم الحليمي البشري عالي الخطورة في باكستان. من خلال التحليل التطوري، تم اكتشاف أن جينوم فيروس الورم الحليمي البشري-16 المعزول في هذه الدراسة له بنية وراثية مميزة وكان له أيضا أوجه تشابه مع الجينومات المبلغ عنها من تايلاند والولايات المتحدة والهند والصين وأوروبا. Abstract: Introduction/objectives: Head and neck region squamous cell carcinoma (HNSCC) is a heterogeneous disease that can be categorized into human papillomavirus (HPV)-positive (20 %) and HPV-negative (80 %) subtypes. However, the prevalence of HPV genotypes is not clear in Pakistan. This study investigated how common the HPV-16 genotype is in patients with HNSCC in the Southern Punjab region of Pakistan, and the specific molecular features of this genotype. Methods: For this cross-sectional study, 85 tissue samples were collected from diagnosed cases of HNSCC. Formalin-fixed paraffin-embedded tissue sections were used for genomic DNA extraction. The L1 region was amplified using GP5+ and GP6+ primers to detect HPV DNA. Real-time PCR was conducted to genotype high-risk HPV (HR-HPV). Whole genome sequencing was used for phylogenetic analysis of HPV-16 and to detect mutations/single nucleotide polymorphisms (SNPs). Results: Among the 85 samples, 7.1 % were positive for HPV, where 4.7 % were positive for HPV-16 and 2.4 % were positive for HPV-18. A significant association was found between HR-HPV positivity and histological grade (p < 0.05). The HPV-16 genome sequence obtained in this study was closely related to those from Thailand, the United States, India, China, and Europe, and 11 mutations/SNPs were detected in the sequenced genome, where four were novel. Conclusion: The findings obtained in the present study demonstrate the low prevalence of HR-HPV associated HNSCC in Pakistan. Phylogenetic analysis showed that HPV-16 genome isolated and sequenced in this study had a distinct genetic structure and it also shared similarities with genomes reported from Thailand, the United States, India, China, and Europe.